Stimulus Shares for Employees of Private Joint Stock Companies: Comparative study - Ali Alrahoo; Ghayib Midhat (الرافدین للحقوق, 2023)
The capital in joint-stock companies is of great importance due to its role in achieving the company’s goals and employing it in the conduct of its affairs. Therefore, we find concerted efforts between the founders and subscribers in collecting the necessary funds to achieve this goal. The personal scope of ownership as an effective means to achieve the participation of workers in the ownership of the capital, as an exception to the traditional rules of ownership of shares, which restricted the ownership of capital to its shareholders. Legally defined, in appreciation of their efforts in managing the company’s affairs.